The Effect of Binahong (Anredera cordifolia (Ten.) Steenis) Leaf Ethanolic Extract on the Reduction of Blood Uric Acid Levels in Hyperuricemic Male White Wistar Rats (Rattus norvegicus) - Anugerah, Panji; Rahman, Safrizal (Folia Medica Indonesiana, 2023)
Highlights: • Antioxidant flavonoid compounds can be found in binahong leaf extract. • Binahong leaf extract is as effective as allupurinol in reducing uric acid levels. Abstract: Binahong (Anredera cordifolia (Ten.) Steenis) is empirically used to treat burns, rheumatism, gout, typhoid, and stroke. Binahong leaves contain flavonoids that have an antioxidant effect. This study aimed to identify and test binahong leaf flavonoid compounds' antioxidant properties in reducing uric acid levels. This study began by producing binahong leaf extract and then identifying the flavonoid content with a phytochemical test. The results indicated that the binahong leaf extract contained antioxidant flavonoid compounds. The data were followed by testing flavonoid activity in lowering uric acid levels. This study used male white Wistar rats, of which the uric acid was induced by chicken liver juice. The animals used in the test were 25 rats divided into five groups (i.e., negative control group, positive control group, and treatment groups with dose I, dose II, and dose III). In each group, there were five male white rats. This study was a laboratory experiment using a pre-test post-test design with control groups (pre-test post-test control group design), where the grouping was done based on a randomized group design. By using statistical tests, the results obtained showed that there was a significant decrease of uric acid levels in the positive control group and the treatment group. In conclusion, binahong leaf ethanolic extract can reduce blood uric acid levels induced by chicken liver juice in male white Wistar rats.